2014
DOI: 10.5755/j01.ee.25.5.4531
|View full text |Cite
|
Sign up to set email alerts
|

Effective Tax Rates in Corporate Taxation: a Quantile Regression for the EU

Abstract: In this work we study the determinants of the effective tax rates for corporate taxation in countries of the European Union. First, we carry out an exhaustive review of the empirical literature where no consensus is reached about the signs of the determinants and we can observe that in the case of the European countries this topic has scarcely received attention, contrary to the US case. Then from the Compustat database and for the period 1992-2009, we estimate quantile regressions that allow possible nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 42 publications
3
54
1
6
Order By: Relevance
“…Based on the research results Richardson et al (2016), Kraft (2014), and Delgado et al (2014) shows that there is a significant correlation between the profitability of the company with tax evasion. Different with Zarai research (2013) indicates that the higher profitability of the company will be the higher effective tax rate, which means that the lower the tax evasion by the company while the research results Prakosa (2014) found that the return on assets negatively affects tax evasion.…”
Section: Introductionmentioning
confidence: 94%
“…Based on the research results Richardson et al (2016), Kraft (2014), and Delgado et al (2014) shows that there is a significant correlation between the profitability of the company with tax evasion. Different with Zarai research (2013) indicates that the higher profitability of the company will be the higher effective tax rate, which means that the lower the tax evasion by the company while the research results Prakosa (2014) found that the return on assets negatively affects tax evasion.…”
Section: Introductionmentioning
confidence: 94%
“…Income is computed as taxable revenues reduced by eligible costs incurred to generate, assure or maintain taxable income, subject to additional tax adjustments. From the international perspective, corporate income tax has been characterized in recent years by a gradual decrease of the nominal tax rate and the countries of the EU are no exception (Delgado et al, 2014). The corporate income tax has developed also in the Slovak Republic.…”
Section: G-g P H-f Epsilonmentioning
confidence: 99%
“…Those explanations are in line with the prior research that found a negative association between leverage and ETR (Di and Hua, 2013;Lazar, 2014;Kraft, 2014;Stamatopoulus, 2016). However, Wang et al (2014), and Delgado et al, (2014) discovered that the more corporates rely on debt, the higher their ETR. On the other hand, the study conducted by Ardyansah and Zulaikha (2014) found that leverage does not influence ETR.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the greater the proportion of fixed assets in total assets, the lower the ETR (Lazar, 2014;Stamatopaolus, 2016). Conversely, Darmadi and Zulaikha (2013), Ardyansah and Zulaikha (2014), and Delgado et al (2014) discovered that the higher the amount of fixed assets, the higher the ETR. Study by Liu and Cao (2007) and Di and Hua (2013) found that density of fixed assets does not influence ETR.…”
Section: Introductionmentioning
confidence: 99%